2014
DOI: 10.1016/j.aquaculture.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoal capacitation of pink shrimp Farfantepenaeus paulensis

Abstract: The present study evaluated spermatozoal capacitation in Farfantepenaeus paulensis. This process has direct applications in aquaculture, and it consists of the ionic, biochemical and morphological changes during the period that the spermatophore is stored or adhered to the thelycum. These changes make the spermatozoa capable of fertilization. The morphological changes of spermatozoal capacitation have been previously investigated only in sicyoniids and open-thelycum penaeids. Thus, this study is the first morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 23 publications
5
20
1
Order By: Relevance
“…Our study showed the subacrosomal area of P. monodon spermatozoa in the spermatophore appeared less electron‐lucent and flocculent than the capacitated spermatozoa in the thelycum, as noted by Pongtippatee et al (). The subacrosomal change of P. monodon during capacitation also coincides with the similar observations of sperm capacitation in F. paulensis (Braga et al, ) and L. vannamei (Alfaro et al, ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our study showed the subacrosomal area of P. monodon spermatozoa in the spermatophore appeared less electron‐lucent and flocculent than the capacitated spermatozoa in the thelycum, as noted by Pongtippatee et al (). The subacrosomal change of P. monodon during capacitation also coincides with the similar observations of sperm capacitation in F. paulensis (Braga et al, ) and L. vannamei (Alfaro et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the electron density of the spike appeared to be lower in spermatophoral sperm of P. monodon, when it was compared to thelycal capacitated sperm (Pongtippatee et al, 2007). A similar pattern of morphological change has also been observed between noncapacitated and capacitated sperm in F. paulensis and L. occidentalis (Alfaro et al, 2007;Braga et al, 2014).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The freshly ejaculated spermatophore is soft in decapods, but after mating it becomes hardened to protect the sperm mass (Malek and Bawab, 1971;Uma and Subramoniam, 1979). Post-mating spermatophore storage in crayfish and other decapods is accompanied by morphological and molecular changes that are necessary for the spermatozoon to develop fertilizing ability (Alfaro et al, 2003;Vanichviriyakit et al, 2004;Alfaro et al, 2007;López Greco and Lo Nostro, 2008;Aungsuchawan et al, 2011;Braga et al, 2014;Niksirat et al, 2014bNiksirat et al, , 2015b.…”
Section: Biology Of Gametes In the Crayfishmentioning
confidence: 99%